Decontamination of petroleum-contaminated soil via pyrolysis under carbon dioxide atmosphere. (1st November 2019) - Kim, Youkwan; Oh, Jeong-Ik; Lee, Sang Soo; Lee, Kyun Ho; Lee, Jechan; Kwon, Eilhann E.
Abstract: Accidental leakage and/or spillage of crude oil contaminates soil occurring during petroleum extraction, which can have harmful effects both on the environment and human beings. Therefore, petroleum-contaminated soil needs to be effectively decontaminated. As a study of thermal remediation of petroleum-contaminated soil, a real soil sample contaminated with petroleum was pyrolyzed at different pyrolysis conditions. In particular, carbon dioxide (CO2 ) was used as the pyrolysis medium for effective thermal remediation of the petroleum-contaminated soil. At temperatures above 620 °C, pyrolytic gas evolution patterns obtained in CO2 condition were distinguishable from those obtained in N2 condition; the generation of carbon monoxide (CO) was observed. The formation of CO at temperatures higher than 620 °C might be a clue about the role of CO2 in pyrolysis of the petroleum-contaminated soil in that CO2 helps form CO via reactions between CO2 and volatile species evolved from the petroleum hydrocarbons deposited on the soil during the pyrolysis. For further investigating the effect of CO2 on the pyrolysis, two-stage pyrolysis of the petroleum-contaminated soil was conducted. The CO evolution also occurred in the CO2 condition during the two-stage pyrolysis at >210 °C. The different compositions of pyrolytic oil obtained from the pyrolysis in N2 and CO2 were identified in that the formation of polycyclic aromatic hydrocarbons was restricted by the consuming the source of carbon. The pyrolysis operated under CO2 atmosphere would be an effective decontamination method to treat petroleum-contaminated soil. Highlights: Enhanced production of CO via using CO2 in pyrolysis of petroleum-contaminated soil. Enhanced thermal cracking of volatile species caused by CO2 in the pyrolysis. Two-stage pyrolyzer to provide a precise observation in effect of CO2 on the pyrolysis. Pyrolysis in CO2 would be an effective remediation of petroleum-contaminated soil.